2005
DOI: 10.1620/tjem.205.133
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Clopidogrel on Oxidant Damage in A Rat Model of Acute Ischemia

Abstract: Reperfusion injury is a consequence of inadequate energy supply and acidosis in ischemic tissues and a chain of events triggered by oxygen-derived free radicals released in response to exposure of oxygen. In this study, we aimed to assess the effects of clopidogrel, an antithrombotic agent, on experimental ischemia-reperfusion model in rats. The ischemia was performed by blockade of the circulation of right lower extremity at trochanter major level for 6 hours. Then, the extremity was reperfused for 4 hours. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 25 publications
(16 reference statements)
3
25
1
Order By: Relevance
“…36 Consistent with our results, some studies have shown the same pattern in liver and pancreas injury. 37,38 Our findings suggest that other compensatory mechanisms may be protecting the MT KO mice from elevated oxidative stress after ischemia.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…36 Consistent with our results, some studies have shown the same pattern in liver and pancreas injury. 37,38 Our findings suggest that other compensatory mechanisms may be protecting the MT KO mice from elevated oxidative stress after ischemia.…”
Section: Discussionsupporting
confidence: 93%
“…MT and its downstream targets therefore might provide therapeutic targets for enhancing collateral development. Moreover, because each of the cell types we describe that are affected by MT are known contributors not only to collateral vessel development but also to atherogenesis, 36 our findings suggest that further investigation of MT protein levels and polymorphisms may provide useful biomarkers or therapeutic targets for patients with cardiovascular disease.…”
Section: Resultsmentioning
confidence: 82%
“…The production of ROS increases considerably during tissue ischemia due dissociation of oxidative phosphorylation, which results in univalent reduction of oxygen, catabolism of ATP into hypoxanthine and uric acid and infiltration of damaged tissues by polymorphonuclear leukocytes (Rogacka et al 2000;Kanko et al 2005). Zhao et al (2000) demonstrated the peak of neutrophil accumulation to occur between 6 and 24 hrs after myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…3 Consistent with this, platelet depletion or inhibition of platelet activation improves microvascular perfusion and reduces tissue inflammation and injury. [4][5][6][7] Experimental and clinical evidence has demonstrated that thrombi are highly efficient at recruiting leukocytes from flowing blood 8 with the extent of the thromboinflammatory response correlating with the degree of organ injury and clinical outcome. 9 Despite its clinical importance, there is limited understanding of the mechanisms by which microvascular thrombi guide leukocytes to sites of vascular injury.…”
Section: Introductionmentioning
confidence: 99%